TINJAUAN YURIDIS FUNGSI COORPORATE SOCIAL RESPONSIBILITY (CSR) BAGI PERKEMBANGAN PERSEROAN TERBATAS (PT) MENURUT UU NO. 40 TAHUN 2007 (Studi : Pada PT. Medan Jaya Cipta Sarana) - Hari Tamara (JURNAL CIVIL LAW USU, 2013)
Abstract : Corporate Social Responsibility (CSR) is a program made ​​by a company as a form of social responsibility and concern for the community and appropriate stakeholders are mandated by Act No. 40 of 2007 on Limited Liability Companies. However, we need to realize that CSR is not just a social program established. Although the primary objective of any company is looking for profit maximization, but it should be thought of as narrow as this should be left behind. The concept of community economic sustainability while improving the quality of life of employees and their families and local communities and the public at large the original purpose of the establishment of CSR by the World Business Council for Suintanable Development.   Keywords : Coorporate Social Responsibility, Perseroan Terbatas